2020
DOI: 10.18231/j.ijceo.2020.021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of diabetic retinopathy and systemic complications of diabetes

Abstract: : To study the relationship of diabetic retinopathy with systemic complications of diabetes.: Study was conducted on 310 diabetic patients attending to Narayana medical college ophthalmology opd in Nellore between August 2017and June 2018. Patients are categorized into five groups based on the duration and severity of DR into No DR, Mild NPDR, ModerateNPDR, Severe NPDR, PDR according to the ETDRS classification. All the above patients evaluated clinically, and required investigations were done for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This findings were consistent with Vidyashri, et al (2021) [20] who conducted study on 800 DPs and found that the most common associated systemic complication observed was hypertension (32.57%) and also consistent with Dregan, et al (2014) [28] who found that hypertension was more prevalent. Whilst inconsistent with Priya, et al (2020) [29] who carried study on 310 DPs and revealed that the most common systemic complication was diabetic retinopathy (34.8%) and also inconsistent with Bajaj, et al (2012) [30] who reported that retinopathy was significantly more prevalent in DPs. Teeth loss as an indicator for oral health reputation has a more potent association with risk of diabetes complications.…”
Section: Discussionmentioning
confidence: 90%
“…This findings were consistent with Vidyashri, et al (2021) [20] who conducted study on 800 DPs and found that the most common associated systemic complication observed was hypertension (32.57%) and also consistent with Dregan, et al (2014) [28] who found that hypertension was more prevalent. Whilst inconsistent with Priya, et al (2020) [29] who carried study on 310 DPs and revealed that the most common systemic complication was diabetic retinopathy (34.8%) and also inconsistent with Bajaj, et al (2012) [30] who reported that retinopathy was significantly more prevalent in DPs. Teeth loss as an indicator for oral health reputation has a more potent association with risk of diabetes complications.…”
Section: Discussionmentioning
confidence: 90%